Pengembangan media video animasi berbantuan Canva dengan menggunakan model problem based learning untuk meningkatkan kemampuan berpikir kritis siswa kelas V Sekolah Dasar - Isni Nuraeni Fazri; Wikanengsih; D Fadly Pratama (IKIP Siliwangi, 2026)
AbstractThe development of digital techonology brings significant changes in the learning process, but science learning process, but science learning in elementary schools still shows limitations in the use of interactive media and students’ critical thinking skills are not optimal. This study aims to develop and test the feasibility and effectiveess of Canva assisted animated video media integreted with the Problem Based Learning (PBL) model to improve students’s critical thinking skills. This study uses the Research and Development (R&D) method with the Borg and Gall model modified into eight stages. The effectiveness test wass conducted using a one-group pretest-posttest desgin on fifth-grade students. Data were obtained through expert validation sheets, observations, response questionnaires, and critical thinking ability tests that included three analysis indicators, namely, evaluation, and inferencec, then analyzed using percentages, n-gain, and paired sample t-test. The results of the study showed that the developed media was categorized as very feasible. Student responses were catogerized as positive at 78%. The results of the pretest and posttest showed an increase in the average score from 56.00 to 83.20 with an n-gain value of 0.63 (moderate category). The result of statistical test showed a significant difference (p < 0.001). These findings show that the integration of PBL in animated video media is able to create more meaningful learning and improve students’ critical thinking skills. Keywords: Animated Video, Problem Based Learning, Critical Thinking Abstrak Perkembangan teknologi digital membawa perubahan besar dalam proses pembelajaran, namun pembelajaran IPAS di sekolah dasar masih menunjukkan keterbatasan dalam penggunaan media interaktif dan kemampuan berpikir kritis siswa yang belum optimal. Penelitian ini bertujuan untuk mengembangkan dan menguji kelayakan serta efektivitas media video animasi berbantuan Canva yang diintegrasikan dengan model Problem Based Learning (PBL) untuk meningkatkan kemampuan berpikir kritis siswa. Penelitian ini menggunakan metode Research and Development (R&D) dengan model Borg and Gall yang dimodifikasi menjadi delapan tahap. Uji efektivitas dilakukan menggunakan desain one-group pretest-posttest pada siswa kelas V. Data diperoleh melalui lembar validasi ahli, observasi, angket respon, dan tes kemampuan berpikir kritis, kemudian dianalisis menggunakan persentase, n-gain, dan uji paired sample t-tets. Hasil penelitian menunjukkan bahwa media yang dikembangkan termasuk kategori sangat layak. Respon siswa tergolong positif sebesar 78%. Hasil pretest dan posttest menunjukkan peningkatan nilai rata-rata 56,00 menjadi 83,20 dengan nilai n-gain 0,63 (kategori sedang). Hasil uji statistik menunjukkan adanya perbedaam yang signifikan (p < 0,001). Temuan ini menunjukkan bahwa integrasi PBL dalam media video animasi mampu menciptakan pembelajaran yang lebih bermakna dan meningkatkan kemampuan berpikir kritis siswa. Kata Kunci: Vidio Animasi, Problem Based Learning, Berpikir Kritis